25.0k views
3 votes
What is y=4x and y=-2x-6 using substitution

2 Answers

6 votes


y = 4x \\ y = - 2x - 6 \\ 4x = - 2x - 6 \\ 6x = - 6 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: x = - 1 \\ y = 4( - 1) \\ y = - 4
User Imgkl
by
6.2k points
4 votes
Hey there!

In solving systems of equations, substitution is the method where you plug equations in for other variables. In this, because both equations are set equal to y, the values of the equations will be equal to one another, therefore, you can substitute one of the equations in place of y.

This should look like this:
4x=-2x-6

Now, add 2x to both sides in order to cancel -2x on one side so that you can isolate your x term:
4x=-2x-6
+2x +2x
6x=-6

Now, divide both sides by 6 to isolate x to get x=-1.

Now that you have the value of x, plug this value into one of the equations to find the value of y:
y=4x
x=-1
y=4(-1)
y=-4

Therefore, y=-4.

Now that you have the values of x and y, your final answer should be x=-1 and y=-4 or (-1,-4).

Hope this helps and have a marvelous day! :)
User LynchburgExplorer
by
6.0k points